Challenges of New Healthcare Reform Act 2017 and Possibility of Rise of Defensive Medicine in Nepal - Acharya, Yogesh; Dahal, Ranjan; Bista, Navindra Raj; Bista, Sangita (Journal of Nepal Health Research Council, 2018)
Hippocratic oath, written 4th or 5th century BC, is still the binding mantra for physicians, which swears to fulfill to the best of one’s ability and judgement, and treat sick human beings not just illness. But with changing health trends in southeast Asia region, there is a dramatic shift in patients and patients’ party expectations regarding treatment, recovery, complications, and death. Such expectations havelead to violence against physicians and shift towards alternative medical practice. This article explores the possible rise of defensive medicine and its broader implications in health care system in Nepal with regard to the new “Muluki Aparadh Samhita Ain 2074/Criminal Code Act 2017”.